Analysis of Factors Associated with Household Waste Production in Antang Landfiil, Tamangapa Village, Manggala District - Zulkarnaen, Iskandar; Pannyiwi, Rahmat; Hardianti, Hardianti; Singga, Siprianus; B, Muslimin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The Antang Final Disposal Site is a reality of life that not many people look into. The Makassar city rubbish dump is the final point for all rubbish trucks in the center of the city. Thus, the Antang Final Disposal Site becomes a center for landfills where it may take years to manage all the collected waste. Apart from being a place to collect rubbish, the Antang Final Disposal Site is also a place to earn a fortune for those who live there. Not a few depend on their profession as garbage collectors. Starting from the head of the family to their children and wives. The aim of this research is to determine the relationship between factors and household production waste at the Antang Tamangapa Final Disposal Site, Makassar City. Based on the results of the research and discussion previously stated, it can be concluded that there is a significant relationship between the variables of number of family members or household residents (p=0.029<0.05, OR=2.941), socio-economic status (p=0.035<0 .05, OR=2.909) with household waste production variables.